Implementasi Rakrutmen Calon Pegawai Negari Sipil Di Badan Kapegawaian Daerah Kabupaten Kepulauan Talaud - SILVIA MALUTU; MASJE PANGKEY; JANTJE MANDEY (JURNAL ADMINISTRASI BISNIS, 2014)
The recruitment process is to obtain human resources activities for the benefit of theincrease in public services according to the needs that have been planned in advance. The purpose ofCPNS course to meet in accordance with job vacancies to be filled by reason of the development oforganizations and fulfill vacancies left by his predecessor as occupying retirement, stopping at his ownrequest or dismissed for violating discipline. Politicization of the bureaucracy which often occurs inpolitical parties vying for control of the ministry. It is also an impact to the CPNS recruitment andposition determination is not objective. And problem for the sake of any procurement CPNSrecruitment. Even this is often the case in any civil servant recruitment process in the Talaud Islands.Therefore, it needs to be held more research on the "Implementation of Recruitment Candidates forthe Civil Service Regional Employment Board Talaud Islands".Research the type used in this study is a qualitative method. Informants in this study as manyas 10 people. Collecting data in this study conducted by methods / techniques interview, observation,secondary data collection to data analysis technique is a qualitative descriptive analysis.The analysis of this study in accordance with the theory of the indicator concerned with thisstudy are (1) aspects of communication, (2) aspects of resources (3) aspects of the disposition (4)aspects of organizational structure.Based on the results of research in the Regional Employment Board Talaud Islands seen fromall four (4) aspects of the indicator is quite good but can not say either. Based on the conclusions of thisstudy, it can be recommended as a general suggestion for Regional Employment Board Talaud Islands,in order to optimize the available resources in the Talaud Islands Regional Employment Board andextended care facilities in order to support themselves.Keywords : Implementation, Recruitmen